2014
DOI: 10.1051/0004-6361/201322681
|View full text |Cite
|
Sign up to set email alerts
|

Mean-field and direct numerical simulations of magnetic flux concentrations from vertical field

Abstract: Context. Strongly stratified hydromagnetic turbulence has previously been found to produce magnetic flux concentrations if the domain is large enough compared with the size of turbulent eddies. Mean-field simulations (MFS) using parameterizations of the Reynolds and Maxwell stresses show a large-scale negative effective magnetic pressure instability and have been able to reproduce many aspects of direct numerical simulations (DNS) regarding growth rate, shape of the resulting magnetic structures, and their hei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
53
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 28 publications
(74 citation statements)
references
References 35 publications
19
53
2
Order By: Relevance
“…Recent DNS using isothermal layers have shown that strong circular flux concentrations can be produced in the case of a vertical magnetic field (Brandenburg et al , 2014. This is also observed in the present study of a polytropic layer; see Fig.…”
Section: Vertical Fieldssupporting
confidence: 89%
See 3 more Smart Citations
“…Recent DNS using isothermal layers have shown that strong circular flux concentrations can be produced in the case of a vertical magnetic field (Brandenburg et al , 2014. This is also observed in the present study of a polytropic layer; see Fig.…”
Section: Vertical Fieldssupporting
confidence: 89%
“…While NEMPI with horizontal magnetic field still leads to downflows in the nonlinear regime (the "potato-sack" effect), our present work now confirms that structures consisting of vertical A2, page 10 of 11 fields do not sink, but reach a strength comparable to or in excess of the equipartition value (Brandenburg et al , 2014. This makes NEMPI a viable mechanism for spontaneously producing magnetic spots in the surface layers.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In the above-mentioned studies the field concentrations often form a spot-like structure because the ratio between the domain size and forcing scale is sufficiently large (e.g. Brandenburg et al 2013Brandenburg et al , 2014Losada et al 2014). …”
Section: Imposed Vertical Fieldmentioning
confidence: 99%